2012
DOI: 10.1183/09059180.00001612
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping immunoglobulin G4-related disease and Rosai–Dorfman disease mimicking lung cancer

Abstract: Bronchial rupture related to endobronchial stenting in relapsing polychondritisTo the Editor:Relapsing polychondritis is a rare multi-systemic disease characterised by recurrent episodes of inflammation and destruction of cartilaginous structures [1]. Airway involvement by relapsing polychondritis, which results in tracheobronchomalacia and airway stenosis, is associated with a poor prognosis.Several reports have suggested that endobronchial intervention can be beneficial in these subjects [2,3]. Herein, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The relationship between RDD and IgG4-RD, not only in skin 8 but also in lung, [26][27][28] breast, 29 heart, 30 parotid, 31 and colon, 32 has been studied in case reports or small series and in 2 recent relatively large series of cases of nodal and extranodal RDD. 24,33 Zhang et al 24 found a mild increase in the absolute number of IgG4+ cells in 19/26 and a IgG/IgG4 ratio greater than 40% in 8/26 RDD specimens, with significantly higher numbers of FOXP3 T regulatory cells (which, together with T-helper 2 cells, regulate the production of IgG4+ cells) in RDD than in controls.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between RDD and IgG4-RD, not only in skin 8 but also in lung, [26][27][28] breast, 29 heart, 30 parotid, 31 and colon, 32 has been studied in case reports or small series and in 2 recent relatively large series of cases of nodal and extranodal RDD. 24,33 Zhang et al 24 found a mild increase in the absolute number of IgG4+ cells in 19/26 and a IgG/IgG4 ratio greater than 40% in 8/26 RDD specimens, with significantly higher numbers of FOXP3 T regulatory cells (which, together with T-helper 2 cells, regulate the production of IgG4+ cells) in RDD than in controls.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, in the IgG4-associated classical RDD, a polyclonal proliferation of IgG4 positive plasma cells and high levels of plasma IG4 levels are observed [158]. This is possibly representing a continuum of RDD to the recently defined nosological entity of IgG4-related disease, which is a chronic immune-mediated fibro-inflammatory condition involving multiple organs, like exocrine and endocrine glands, orbit, retroperitoneum [30,63,158]. Organ fibrosis or sclerosis with infiltration by IgG4 positive plasma cells may lead to secondary organ dysfunction, requiring systemic therapy, which is mainly based on steroids [30].…”
Section: Igg4-associated Classical Rddmentioning
confidence: 99%
“…Further, IgG4 levels may be used as a marker for disease activity. The causal relationship between RDD and IgG4 syndrome, however, is still not quite clear [63,159,226,235].…”
Section: Igg4-associated Classical Rddmentioning
confidence: 99%
“…RDD, a disease characterized by non-clonal S100 positive histiocyte proliferation, shows a lymphangitic distribution on imaging and IgG4þ plasma cell infiltrates in tissues [44]. Overlapping histopathologic findings of IgG4-RD and RDD have been observed in some patients [45,46]. Although RDD is rare, its relationship to IgG4-RD requires further study.…”
Section: Rosai-dorfman Disease (Rdd)mentioning
confidence: 99%